in Quantitative Aptitude edited by
41 views
1 vote
1 vote
If $\text{a,b,c}$ are non-zero and $14^{a} = 36^{b} = 84^{c},$ then $6b \left( \frac{1}{c} – \frac{1}{a} \right)$ is equal to
in Quantitative Aptitude edited by
by
1.3k points 5 6 33
41 views

1 Answer

1 vote
1 vote

Given that, $a,b,c$ are non-zero.

And, $ 14^{a} = 36^{b} = 84^{c} $

We can do the prime factorization.

$ \Rightarrow (2 \times 7)^{a} = (4 \times 9)^{b} = (7 \times 12)^{c} $

$ \Rightarrow 2^{a} \times 7^{a} = (2^{2} \times 3^{2})^{b} = (7 \times 2^{2} \times 3)^{c}$

$ \Rightarrow 2^{a} \times 7^{a} = 2^{2b} \times 3^{2b} = 7^{c} \times 2^{2c} \times 3^{c} $

On comparing, we get,  $ a = 2b = 2c $

Then, $ 6b \left( \frac{1}{c} – \frac{1}{a} \right) = 6b \left( \frac{1}{b} – \frac{1}{2b} \right)  = 6b \left( \frac{2-1}{2b} \right)  = 3 $

$\therefore$ The value of $ 6b \left( \frac{1}{c} – \frac{1}{a} \right) = 3.$


$\textbf{Second Method:}$

Let $ 14^{a} = 36^{b} = 84^{c} = x \; \longrightarrow (1) $

Now, $14^{a} = x$

Taking $\log_{14}$ on both sides

$ \log_{14} 14^{a} = \log_{14}x $

$ \Rightarrow a \log_{14} 14 = \log_{14}x \quad [ \because \log_{a}b^{x} = x \log_{a}b] $

$ \Rightarrow \boxed{a = \log_{14}x} \quad [ \because \log_{a}a = 1] $

$ \Rightarrow \boxed{\frac{1}{a} = \log_{x}14} \quad \left[ \because \log_{a}b = \frac{1}{\log_{b}a}\right] $

Again, $36^{b}  = x$

Taking $\log_{36}$ on both sides.

$ \log_{36}36^{b} = \log_{36}x $

$ \Rightarrow \boxed{b = \log_{36}x} $

Again, $ 84^{c} = x $

Taking $\log_{84}$ on both sides.

$ \log_{84}84^{c} = \log_{84}x $

$ \Rightarrow \boxed{c = \log_{84}x} $

$ \Rightarrow \boxed{\frac{1}{c} = \log_{x}84} $

Then, $ 6b \left( \frac{1}{c} – \frac{1}{a} \right)  = 6 \log_{36}x \left( \log_{x}84 – \log_{x}14 \right) $

$\qquad  = 6 \log_{36}x \left[ \log_{x} \left( \frac{84}{14} \right) \right] \quad \left[ \because \log_{a}m – \log_{a}n = \log_{a} \left( \frac{m}{n} \right)\right] $

$\qquad = 6 \log_{36}x  \cdot \log_{x}6 $

$\qquad = 6 \left( \frac{\log_{c}x}{\log_{c}36} \right) \left( \frac{\log_{c}6}{\log_{c}x} \right) \quad \left[ \because \log_{m}n = \frac{\log_{c}n}{\log_{c}m}\right] $

$\qquad = 6 \left( \frac{\log_{c}6}{\log_{c}6^{2}} \right) $

$\qquad = 6 \left( \frac{\log_{c}6}{2 \log_{c}6} \right) $

$\qquad = 3 $

Correct Answer$: 3$

edited by
by
4.9k points 3 7 28
Answer:

Related questions

Ask
Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true